Handheld swept-source optical coherence tomography with angiography in awake premature neonates - Moshiri, Yasman; Legocki, Alex T.; Zhou, Kanheng; Cabrera, Michelle T.; Rezaei, Kasra A.; Tarczy-Hornoch, Kristina; Wang, Ruikang K. (Quantitative Imaging in Medicine and Surgery, 2019)
Background: Retinopathy of prematurity (ROP) can lead to retinal detachment and severe vision loss and is a common cause of childhood blindness. Optical coherence tomography angiography (OCTA) is a non-invasive imaging modality that can be used to detect potential abnormalities in the microvasculature in this population. The objective of this study is to assess the feasibility of a newly developed handheld swept source OCT (SS-OCT) device to successfully acquire structural vitreoretinal and retinal microvascular images in awake premature infants. Methods: OCT and OCTA images were acquired at the time of routine ROP examinations from awake, unsedated preterm infants in the Neonatal Intensive Care Unit using a clinical research prototype handheld probe integrated with an SS-OCT system working at 1,060 nm wavelength and an imaging speed of 200,000 A-scans per second (200 kHz), enabling volume OCT and OCTA scans. Each volume was acquired with approximately 36˚ field of view (~6.3×6.3 mm in infants) in 4.8 s. Quality of acquired OCT and OCTA volume images, microvascular information, and vitreoretinal features were determined by 3-masked grader consensus. Results: Twelve infants (5 females, mean gestational age 28.3 weeks, median birth weight 901 g, stages 0 to 3 ROP) underwent a total of 73 individual eye imaging sessions. High-quality OCT images of the fovea and the optic nerve were present in 69/73 (94.5%) and 56/73 (76.7%) scans, respectively. Vitreous bands were observed in 10/73 (13.7%); punctate hyperreflective vitreous opacities in 47/73 (64.4%); epiretinal membrane (ERM) in 6/73 (8.2%); and cystoid macular edema (CME) in 12/73 (16.4%) scans. Mild vessel elevation was noted in 3/73 (4.1%) images, and severe vessel elevation in 4/73 (5.5%) scans. OCTA images obtained in 8 awake infants revealed good quality images of the foveal microvasculature in 11/19 (58%) eye imaging sessions for 6/8 (75%) infants; and peripapillary microvasculature in 14/19 (74%) eye imaging sessions for 5/8 (63%) infants. Conclusions: The SS-OCTA handheld device can capture important vitreoretinal characteristics such as peripapillary and foveal microvasculature, as well as hyperreflective punctate vitreous opacities and tractional vitreous bands, which may predict ROP severity. These images were captured in awake, premature infants without the use of direct ocular contact, an eyelid speculum, or sedation.